Semiotics of Sexual Harassment Representation in Photocopier: A John Fiske Semiotic Theory of Reality Representation and Ideology - Mohammad Irfan Farraz Haecal; Muliadi Muliadi; Wildan Taufiq (Tunas Harapan Ummat Foundation, 2025)
Sexual harassment is an interesting issue in a nation that was once safe and peaceful, Indonesia. Sexual harassment seizures that get less attention, both from the authorities and the authorities or even have to choose silence when dealing with the more powerful parties often occur. This creates a negative stigma and causes sexual abuse traffickers to be afraid to complain about the crimes that occur to themselves and the absence of a deterrent effect on the perpetrator makes the perpetrators act freely because they feel themselves safe. This phenomenon was made into a Light Confiscation Film Photocopier. The purpose of the researchers in raising this discussion is to describe and represent the case of sexual harassment raised in the film Photocopier. Researchers used analytical techniques using qualitative methods and took John Fiske's semiotic examination methods to pass codes and profound importance on to films. The outcomes showed that the portrayal of sexual brutality in this film there are three phases as per John Fiske covering the degree of the real world, the degree of portrayal and the degree of philosophy inferred from the depiction of sexual violence carried out and concluded that in this film use patriarchal ideology and social class.